PENGARUH MODAL, TENAGA KERJA, BAHAN BAKU, MESIN TERHADAP PRODUKSI INDUSTRI KECIL KONVEKSI DESA PADURENAN KECAMATAN GEBOG KABUPATEN KUDUS - Rudi Wibowo (Economics Development Analysis Journal, 2013)
This study aimed to analyze the influence of capital, labor, raw materials, engine for small industrial production convection in Padurenan Village Gebog Sub-District Kudus Region.. This study used Ordinary Least Square (OLS) method is multiple linear regression analysis. The results showed that the test to the regression coefficients α = 1% and 5% showed four variables of capital, labor, raw materials, engine affects the production of small convection industry in the Padurenan village. The conclusion of this study that there is an influence of capital, labor, raw materials, engine for industrial production of small convection in Padurenan Village Gebog Sub- District Kudus Region at 88.0% and approximately 12.0% described other variables outside the model.